Anti-rheumatoid Activity of Secondary Metabolites Produced by Endophytic Chaetomium globosum - Abdel-Azeem, Ahmed M.; Zaki, Sherif M.; Khalil, Waleed F.; Makhlouf, Noha A.; Farghaly, Lamiaa M. (Frontiers in Microbiology, 2016)
Abstract The aim of the present study was to investigate the anti-rheumatoid activity of secondary metabolites produced by endophytic mycobiota in Egypt. A total of 27 endophytic fungi were isolated from 10 dominant medicinal plant host species in Wadi Tala, Saint Katherine Protectorate, arid Sinai, Egypt. Of those taxa, seven isolates of Chaetomium globosum (CG1 – CG7), being the most frequent taxon, were recovered from seven different host plants and screened for production of active anti-inflammatory metabolites. Isolates were cultivated on half – strength potato dextrose broth for 21 days at 28ºC on a rotatory shaker at 180 rpm, and extracted in ethyl acetate and methanol, respectively. The probable inhibitory effects of both extracts against an adjuvant induced arthritis (AIA) rat model were examined and compared with the effects of methotrexate as a standard disease-modifying anti-rheumatoid drug. Disease activity and mobility scoring of AIA, histopathology and transmission electron microscopy (TEM) were used to evaluate probable inhibitory roles. A significant reduction (P < 0.05) in the severity of arthritis was observed in both the methanolic extract of CG6 (MCG6) and methotrexate (MTX) treatment groups six days after treatment commenced. The average arthritis score of the MCG6 treatment group was (10.7 ± 0.82) compared to (13.8 ± 0.98) in the positive control group. The mobility score of the MCG6 treatment group (1.50 ± 0.55) was significantly lower than that of the positive control group (3.33 ± 0.82). In contrast, the ethyl acetate extract of CG6 (EACG6) treatment group showed no improvements in arthritis and mobility scores in AIA model rats. Histopathology and TEM findings confirmed the observation. Isolate CG6 was subjected to sequencing for confirmation of phenotypic identification. The internal transcribed spacer (ITS) 1 – 5.8s – ITS2 rDNA sequences obtained were compared with those deposited in the GenBank Database and registered with accession number KC811080 in the NCBI Database. The present study revealed that the methanol extract of endophytic fungus C. globosum (KC811080) recovered from maidenhair fern has an inhibitory effect on inflammation, histopathology and morphological features of rheumatoid arthritis in an AIA rat model.